Optimism in financial markets: Stock market returns and investor sentiments - Chiara Concetto Limongi; Francesco Ravazzolo (Journal of Risk and Financial Management, 2019)
This paper investigates how investor sentiment affects stock market returns and evaluates the predictability power of sentiment indices on U.S. and EU stock market returns. As regards the American example, evidence shows that investor sentiment indices have an economic and statistical predictability power on stock market returns. Concerning the European market instead, investigation provides weak results. Moreover, comparing the two markets, where investor sentiment of U.S. market tries to predict the European stock market returns, and vice versa, the analyses indicate a spillover effect from the U.S. to Europe.
Keywords: C11; C22; G11; G12; 330